Lifelong socioeconomic trajectory and premature mortality (35–65 years) in France: findings from the GAZEL Cohort Study. Issue 11 (19th October 2006) - Melchior, M; Berkman, L F; Kawachi, I; Krieger, N; Zins, M; Bonenfant, S; Goldberg, M
Abstract : Background: Studies conducted in the UK and Scandinavia show an inverse association between lifetime socioeconomic position and adult mortality. However, there are virtually no data from other countries and few investigations have examined non-cardiovascular mortality in men and women. Methods: Lifelong socioeconomic trajectories (father's occupation, own occupation in young adulthood and in mid-life) and premature (⩽65 years) mortality (all-cause, smoking-related cancer, diseases of the circulatory system and external causes) in the French GAZEL Cohort Study (14 972 men and 5598 women, followed up between 1990 and 2004) were studied. Hazard ratios (HRs) were estimated using Cox's regression models adjusted for age, marital status, tobacco smoking, alcohol consumption, body mass index, and fruit and vegetable consumption. Results: Men and women who experienced lifelong disadvantage or downward intergenerational mobility were at high risk of dying prematurely compared with those with a favourable trajectory (age-adjusted HRs for all-cause mortality: cumulative disadvantage: HR 1.61, 95% confidence interval (CI) 1.26 to 2.06 in men and HR 1.95, 95% CI 1.10 to 3.47 in women; downward mobility: HR 1.87, 95% CI 1.35 to 2.58 in men and HR 2.05, 95% CI 1.12 to 3.75 in women). Associations were strongest for mortality due to chronic diseases (smoking-related cancers and diseases of the circulatory system). These associations were partly explained by marital status, body mass index, alcohol consumption, cigarette smoking, and fruit and vegetable consumption. Conclusions: In France, where the leading cause of premature death is cancer, lifelong socioeconomic position is associated with the risk of dying before the age of 65 years. Adult factors seem more relevant than childhood socioeconomic circumstances.